Antibacterial, Antibiofilm, and Antioxidant Activity of 15 Different Plant-Based Natural Compounds in Comparison with Ciprofloxacin and Gentamicin - Ali Pormohammad; Dave Hansen; Raymond J. Turner (MDPI AG, 2022)
Plant-based natural compounds (PBCs) are comparatively explored in this study to identify the most effective and safe antibacterial agent/s against six World Health Organization concern pathogens. Based on a contained systematic review, 11 of the most potent PBCs as antibacterial agents are included in this study. The antibacterial and antibiofilm efficacy of the included PBCs are compared with each other as well as common antibiotics (ciprofloxacin and gentamicin). The whole plants of two different strains of Cannabis sativa are extracted to compare the results with sourced ultrapure components. Out of 15 PBCs, tetrahydrocannabinol, cannabidiol, cinnamaldehyde, and carvacrol show promising antibacterial and antibiofilm efficacy. The most common antibacterial mechanisms are explored, and all of our selected PBCs utilize the same pathway for their antibacterial effects. They mostly target the bacterial cell membrane in the initial step rather than the other mechanisms. Reactive oxygen species production and targeting [Fe-S] centres in the respiratory enzymes are not found to be significant, which could be part of the explanation as to why they are not toxic to eukaryotic cells. Toxicity and antioxidant tests show that they are not only nontoxic but also have antioxidant properties in Caenorhabditis elegans as an animal model.